Leucine Rich Repeat Kinase 2 and Innate Immunity - Ahmadi Rastegar, Diba; Dzamko, Nicolas (Frontiers in Neuroscience, 2020)
For more than a decade, researchers have sought to uncover the biological function of the enigmatic leucine rich repeat kinase 2 (LRRK2) enzyme, a large multi-domain protein with dual GTPase and kinase activities. Originally identified as a familial Parkinson’s disease (PD) risk gene, variations in LRRK2 are also associated with risk of idiopathic PD, inflammatory bowel disease and susceptibility to bacterial infections. LRRK2 is highly expressed in peripheral immune cells and the potential of LRRK2 to regulate immune and inflammatory pathways has emerged as common link across LRRK2-implicated diseases. This review outlines the current genetic and biochemical evidence linking LRRK2 to the regulation of innate immune inflammatory pathways, including the toll-like receptor and inflammasome pathways. Evidence suggests a complex interplay between genetic risk and protective alleles acts to modulate immune outcomes in a manner dependent on the particular pathogen and cell type invaded.